Influence of spinning speed on the physical properties of sol-gel spin coated CuO films. (1st November 2020) - Absike, H.; Labrim, H.; Hartiti, B.; Tahri, M.; Ez-Zahraouy, H.
Abstract: In this work, we report the effects of the spin speed on the structural optical and electrical properties of CuO thin films deposited using spin coating technique at different speeds. The phase structure of the produced thin films shows a pure monoclinic structure, with (002) orientation as most intense. The films deposited at 3000 rpm have shown a high absorbance with an optical band gap about 1.83 eV. The electrical conductivity of the elaborated films increases with an increase in coating speed. Our results reveal that the CuO thin films have the potential to be developed in solar cell applications.